Herb-drug interaction potential of anti-borreliae effective extracts from Uncaria tomentosa (Samento) and Otoba parvifolia (Banderol) assessed in vitro - Weiß, Johanna (Molecules, 2019)
Samento (extract from Uncaria tomentosa) and Banderol (extract from Otoba parvifolia) have been demonstrated to have anti-inflammatory and antimicrobial properties, e.g., against different morphological forms of Borrelia burgdorferi. However, there is hardly any data on the pharmacological safety of these two herbal medicines. This in vitro study aimed at scrutinizing their possible characteristics as perpetrators in pharmacokinetic herbal-drug interactions. Inhibition of cytochrome P450 enzymes (CYPs) was quantified by commercial kits and inhibition of drug transporters by use of fluorescent probe substrates. Induction was quantified by real-time RT-PCR and activation of pregnane x receptor (PXR) and aryl hydrocarbon receptor (AhR) by reporter gene assays. Organic anion transporting polypeptide 1B1 (OATP1B1) (IC50 = 0.49 ± 0.28%) and OATP1B3 (IC50 = 0.65 ± 0.29%) were potently inhibited by Banderol, but only weakly by Samento. CYP3A4 was inhibited about 40% at a Samento concentration of 1%. Samento significantly induced mRNA expression of CYP2J2, UGT1A3, UGT1A9, ABCB1, and SLCO1B1 and strongly activated PXR, but hardly AhR. In conclusion, the perpetrator profiles of Samento and Banderol for herb-drug interactions completely differ. Clinical studies are strongly recommended to clarify whether the effects observed in vitro are of clinical relevance.